Justicia radical : una interpretación psicoanalítica de las postdictaduras en España y el Cono Sur - Martín-Cabrera, Luis, 1972-; Concha, Jaime; Abufom, Pablo; Martín-Cabrera, Luis, 1972- (Barcelona : Anthropos, 2016)
This work investigates the convoluted relationship between memory and justice in Spain and the Southern Cone as it is portrayed in political documentaries and detective fiction from Spain and the Southern Cone.
Los desapararecidos de ayer y de hoy / Jaime Concha -- La circulación transatlántica del terror : las paradojas de la desaparición política -- Políticas de la melancolía : la novela negra como parábola del estado de excepción -- La transmisión intergeneracional del trauma en el documental contemporáneo de España y el Cono Sur -- ¿Hacia un modelo de justicia global? : el caso Pinochet y los límites de los derechos humanos y la justicia internacional.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed March 28, 2018)
Keywords: Detective and mystery stories, Spanish -- History and criticism; Detective and mystery stories, Spanish American -- History and criticism; Political persecution in literature; Disappeared persons in literature; Justice in literature; Human rights in literature; Human rights -- Spain; Human rights -- Southern Cone of South America; Electronic books